The effect of the use of encouragement and intimidation on the achievement of primary school students in subject The Holy Quran (Journal of the College of Basic Education, 2023)
There are great scientific efforts made to develop the teaching of Islamic education, striving to keep pace withThe desired scientific progress in teaching this subject, but it is still restricted by teaching methods that prevailed in the past.Its teaching remained based on traditional methods instead of using the most effective teaching methods, as we findIt has neglected the impact of the student in the educational learning process and has given the teacher great attention and given him the impactPioneering in the educational process, contrary to what modern educational trends called for (Al-Saadi,(2000.2.The Islamic Conference held in Makkah Al-Mukarramah (1997) recommended the necessity of expanding the reading ofCompare and memorize it, starting from the elementary stage, with an expansion of interpretation and an accurate understanding of the advanced classes.From the very beginning, the student should accustom himself to the recitation of the Qur’an, pondering its verses, and a broad understanding of its noble meanings.The Almighty (And the Qur’an recited in an astonishing way) (Al-Muzzammil 4) / (Abdullah et al.) 1991: 72.The recommendations of the educational advancement paper came to clarify this, stressing that the student should understand the comparisonThe Holy Qur’an should be fully understood, in addition to the Holy Qur’an, with an integrated scientific approach.And that this be without jurisprudence, and also the necessity of finding and building the foundations of a plan for teaching the Holy Qur’an and education.Islamic principles and applied procedures required in curricula, books, study plans, assessments and examinations.preparation, training, and activities (Nassif et al., 9:1994).The study of (Al-Bazz (1994) recommends research on the need to conduct short refresher courses inThe field of interpretation and recitation with an increase in the practical aspects and practical exercises to increase the competencies of teachers.teachers in that subject, as well as the importance of handing over the responsibility of teaching that subject to teachers with sufficientscientific, as it urges that aspect from the Islamic perspective by overcoming the difficulties of teaching that subject and creatingWays and means of developing it, and stressing the need to prepare the teacher in a way that is consistent with the teaching of that subject (Bazzis,(1994:53 .